Analisis Pengendalian Persediaan Bahan Baku Pada CV. Yan Utama - Dita Alia Farah; Gunarianto; Khojanah Hasan (Bulletin of Management and Business, 2023)
Abstract Control over the supply of raw materials is a must for every company that aims to avoid misuse in the form of fraud or waste, because in the business world problems often occur in carrying out production. The purpose of this study are as follows (1) to determine the raw material inventory control applied to CV. Yan Utama Corporation, (2) to determine the number of orders for CV raw material supplies. Yan Utama Corporation on economical order quantities. This research is a qualitative descriptive research, the location of this research is at CV. Main Yan Company Sidobakti street, Paregi Purwodadi Village. This research technique by way of observation, interviews, and documentation. Data analysis was carried out using a tabular approach and a formula approach. The result of this research is CV. Yan Utama controls the supply of pure chemical raw materials using the EOQ method. The number of orders for raw material inventory CV. Yan Utama on the EOQ is 2,936 kg of raw materials which can be ordered every time an order is placed. The frequency of purchasing raw materials in CV. Yan Utama when using the EOQ method which should or is more efficient is 7 times the purchase of raw materials in one period (1 year), while new orders are made by CV. Main Yan is 24 times a year. So that with this evaluation, the time to order raw materials can be more considered with an interval of every 51 days when ordering pure chemical raw materials. Keywords: Inventory Control, Inventory Orders, Raw Materials.